2- D Slice of Tri- coherency Coefficient Spectrum in the Application of Fault Diagnosis of Marine Gear - Geng Wenfei; Mei Erzhao; Wu Wenbing (Jixie chuandong, 2016)
In order to solve the problem of fault diagnosis of marine gear,a method of comparing 2- D slice of tri- coherency coefficients figure under different frequency of vibration is proposed. Through the sampling data of vibration of marine gear,the tri- coherency function deal with is carried out after preprocessing.The 2- D slice of tri- coherency coefficients figures of data of working vibration of marine gear system are compared under different frequencies,and the result is different obviously. Experiments show that the analysis and diagnosis of 2- D slice of tri- coherency coefficient spectrum are applied to the fault characteristics,which can improve the correct rate of the identification and diagnosis of different fault in some special conditions.